2009
DOI: 10.1074/jbc.m109.020818
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Adaptations to Interrupted Glycosaminoglycan Recycling

Abstract: Lysosomal storage diseases (LSD) are metabolic disorders characterized by accumulation of undegraded material. The mucopolysaccharidoses (MPS) are LSDs defined by the storage of glycosaminoglycans. Previously, we hypothesized that cells affected with LSD have increased energy expenditure for biosynthesis because of deficiencies of raw materials sequestered within the lysosome. Thus, LSDs can be characterized as diseases of deficiency as well as overabundance (lysosomal storage). In this study, metabolite analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
2
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 29 publications
5
32
2
5
Order By: Relevance
“…Given the resemblance of the MPS IIIB mouse model to the human disease, 3 we anticipate that the observed profound metabolic impairments in mice in this study also may occur in patients with MPS IIIB. Previous studies also showed broad metabolomic impairments in the liver in mouse models of MPS I and MPS VII, 38 suggesting profound metabolic abnormalities also may occur in different MPS disorders, given that these closely related diseases share many pathological features.…”
Section: Discussionmentioning
confidence: 99%
“…Given the resemblance of the MPS IIIB mouse model to the human disease, 3 we anticipate that the observed profound metabolic impairments in mice in this study also may occur in patients with MPS IIIB. Previous studies also showed broad metabolomic impairments in the liver in mouse models of MPS I and MPS VII, 38 suggesting profound metabolic abnormalities also may occur in different MPS disorders, given that these closely related diseases share many pathological features.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these metabolic changes showed an activated cell metabolism in the MPS models in comparison with that observed in the healthy state (Recon2) (Supplemental Table 5). Experimental evidence have shown that the cell metabolism in some MPS adapts to the deficiency of recycled substrates through the activation of cell metabolism [49,50].…”
Section: Flux Balance Analysis (Fba)mentioning
confidence: 99%
“…Some of these adverse effects may be responsive to dietary intervention (Woloszynek et al 2009;Meijer and Codogno 2009). …”
Section: Axonal Spheroidsmentioning
confidence: 97%